2008
DOI: 10.1098/rspa.2007.0139
|View full text |Cite
|
Sign up to set email alerts
|

Modal projections for synchronous rotor whirl

Abstract: We consider the synchronous whirl of arbitrary axisymmetric rotors supported on rigid bearings. Prior computational treatments of this problem were based on adding elementlevel gyroscopic terms to the governing equations. Here, we begin with a direct continuum formulation wherein gyroscopic terms need not be added on separately and explicitly: all gyroscopic effects are captured implicitly within the continuum elastodynamics. We present two new methods for obtaining the whirl speed, where we project the dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Three-dimensional finite element analysis of rotors has been attempted by Neogy (2001, 2005). A rigorous general continuum formulation has also been reported for non-axisymmetric rotors on fixed bases (Mahadevan et al, 2008). Lin and Meng (2003) were the first to report on the dynamics of an elastic rotor on a maneuvering support.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional finite element analysis of rotors has been attempted by Neogy (2001, 2005). A rigorous general continuum formulation has also been reported for non-axisymmetric rotors on fixed bases (Mahadevan et al, 2008). Lin and Meng (2003) were the first to report on the dynamics of an elastic rotor on a maneuvering support.…”
Section: Introductionmentioning
confidence: 99%
“…Many sophisticated analyses have been attempted for spinning, symmetric and nonsymmetric shaft-disk systems on fixed base (Nelson and McVaugh, 1976, Nelson, 19801 Ozguven and Ozkan, 19841 Greenhill et al, 19851 Genta and Gugliotta, 19881 Vest and Darlow, 19891 Stephenson and Rouch, 1989, 19931 Gmur and Rodrigues, 19931 Nandi and Neogy, 2003. Apart from numerous finite element analyses of circular and non-circular shafts with multiple disks and three-dimensional analysis of rotors Neogy, 2001, Nandi et al, 2005), a rigorous general continuum formulation has also been recently reported for non-axisymmetric rotors on fixed bases (Mahadevan et al, 2008). It was Lin and Meng (2003), who first reported on dynamics of an elastic rotor on a maneuvering support.…”
Section: Introductionmentioning
confidence: 99%
“…However, if we ignore gravity and seek synchronous whirl solutions, then we must use det(C) = 0, showing that some gyroscopic effects are included in C as well. Mahadevan et al (2008) discussed this issue for continuum rotors. Moving on, following , we introduce…”
Section: Linearizationmentioning
confidence: 99%